Tobacco imagery in Bollywood films: 2006–2008. Issue 1 (16th April 2013) - Nazar, Gaurang P; Gupta, Vinay K; Millett, Christopher; Arora, Monika
Abstract : Objective: To estimate exposure to tobacco imagery in youth-rated Bollywood films, and examine the results in light of recent developments in India's film rating system. Methods: Content coding of 44 top grossing Bollywood films (including 38 youth-rated films) released during 2006–2008 was undertaken to estimate tobacco occurrences and impressions. Results: Out of the 38 youth-rated (U and U/A) films coded, 50% contained tobacco imagery. Mean tobacco occurrences were 1.9, 2.9 and 13.7 per U, U/A and adult (A) rated films, respectively. Top grossing youth-rated films delivered 1.91 billion tobacco impressions to Indian cinema audiences. Conclusions: Half the youth-rated Bollywood films contain tobacco imagery resulting in large population level exposure in India, relative to other countries. Measures to reduce youth exposure to tobacco imagery through films, such as restricting access through the rating system, will complement other tobacco control measures.